Effectiveness of upgraded maternity waiting homes and local leader training on improving institutional births: a cluster-randomized controlled trial in Jimma, Ethiopia - Jaameeta Kurji; Lakew Abebe Gebretsadik; Muluemebet Abera Wordofa; Sudhakar Morankar; Kunuz Haji Bedru; Gebeyehu Bulcha; Nicole Bergen; Getachew Kiros; Yisalemush Asefa; Shifera Asfaw; Abebe Mamo; Erko Endale; et al. (BMC, 2020)
Abstract Background Maternity waiting homes (MWHs), residential spaces for pregnant women close to obstetric care facilities, are being used to tackle physical barriers to access. However, their effectiveness has not been rigorously assessed. The objective of this cluster randomized trial was to evaluate the effectiveness of functional MWHs combined with community mobilization by trained local leaders in improving institutional births in Jimma Zone, Ethiopia. Methods A pragmatic, parallel arm cluster-randomized trial was conducted in three districts. Twenty-four primary health care units (PHCUs) were randomly assigned to either (i) upgraded MWHs combined with local leader training on safe motherhood strategies, (ii) local leader training only, or (iii) usual care. Data were collected using repeat cross-sectional surveys at baseline and 21 months after intervention to assess the effect of intervention on the primary outcome, defined as institutional births, at the individual level. Women who had a pregnancy outcome (livebirth, stillbirth or abortion) 12 months prior to being surveyed were eligible for interview. Random effects logistic regression was used to evaluate the effect of the interventions. Results Data from 24 PHCUs and 7593 women were analysed using intention-to-treat. The proportion of institutional births was comparable at baseline between the three arms. At endline, institutional births were slightly higher in the MWH + training (54% [n = 671/1239]) and training only arms (65% [n = 821/1263]) compared to usual care (51% [n = 646/1271]). MWH use at baseline was 6.7% (n = 256/3784) and 5.8% at endline (n = 219/3809). Both intervention groups exhibited a non-statistically significant higher odds of institutional births compared to usual care (MWH+ & leader training odds ratio [OR] = 1.09, 97.5% confidence interval [CI] 0.67 to 1.75; leader training OR = 1.37, 97.5% CI 0.85 to 2.22). Conclusions Both the combined MWH+ & leader training and the leader training alone intervention led to a small but non-significant increase in institutional births when compared to usual care. Implementation challenges and short intervention duration may have hindered intervention effectiveness. Nevertheless, the observed increases suggest the interventions have potential to improve women's use of maternal healthcare services. Optimal distances at which MWHs are most beneficial to women need to be investigated. Trial registration The trial was retrospectively registered on the Clinical Trials website ( https://clinicaltrials.gov ) on 3rd October 2017. The trial identifier is NCT03299491 .